2011
DOI: 10.1007/s10665-011-9515-z
|View full text |Cite
|
Sign up to set email alerts
|

Dewetted Bridgman crystal growth: practical stability over a bounded time period in a forced regime

Abstract: Dewetted Bridgman crystal growth: practical stability over a bounded time period in a forced regimeSt. Balint · S. Epure · T. Duffar · L. Braescu Abstract The concept of practical stability is applied to the case of dewetted Bridgman crystal growth on Earth, in a simplified configuration. Taking into account both heat transfer and capillarity, it is formally demonstrated that the process is stable in case of convex menisci, provided that pressure fluctuations remain in a range which can be computed. The theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The function ψ (r c , p) obtained for an arbitrary l 0 and h 0 coincides with that obtained applying the same steps for any l = l 0 , l∈(0,H a ) (see Balint et al 2011).…”
Section: Stability Of the Dewetted Bridgman Crystal Growth Process Insupporting
confidence: 63%
See 1 more Smart Citation
“…The function ψ (r c , p) obtained for an arbitrary l 0 and h 0 coincides with that obtained applying the same steps for any l = l 0 , l∈(0,H a ) (see Balint et al 2011).…”
Section: Stability Of the Dewetted Bridgman Crystal Growth Process Insupporting
confidence: 63%
“…It can be shown that the following statement holds (see Balint et al 2011): Statement 1 For 0 < e 1 < e 2 < r a , h ∈ e 2 tan π 2 − α e , e 2 tan θ c − π 2 and p satisfying: there exists r c ∈ [r a − e 2 , r a − e 1 ], l (t) ∈ [l(t) + h − e 2 tan (θ c − π 2 ), l(t) + h − e 1 tan( π 2 − α e )] and a convex solution z(r) (i.e., d 2 z dr 2 > 0) of the initial value problem:…”
Section: Equation Governing the Crystal-crucible Gap Thickness Evolutionmentioning
confidence: 97%
“…Stability analyses, generally based on Lyapunov's approach [17], have been performed for the three models. Simple approaches considering only the capillary effect [9,10] as well as more thorough analyses taking into account coupling between capillarity, heat transfer and pressure fluctuations [18][19][20][21][22][23] give the same result: dewetting is stable only when the meniscus is convex at the liquid-crystal-gas triple line, which means that abnormally high values of y should be considered in order to fulfil relation (1). In the case of model 3, stability also depends on the transport of gas dissolved in the liquid [21].…”
Section: Introductionmentioning
confidence: 99%